2003
DOI: 10.1142/s136391960300088x
|View full text |Cite
|
Sign up to set email alerts
|

New Product Development Practices and Export Involvement: An Initial Inquiry

Abstract: This study is an exploratory investigation into the role of new product development practices in the internationalisation process. Specifically, the relationship among five identified new product development practices and three export involvement stages is explored.The analysis of survey data obtained from a national sample of U.S. manufacturing firms provide support for the contention that certain new product development capabilities must exist at all stages of the internationalisation process. The results fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 83 publications
0
5
0
3
Order By: Relevance
“…The pressure to launch a new product concurrently or ahead of competitors in local and foreign markets is motivated by the emergence of global buyer segments, fear of technological obsolescence, and need for industry leadership in product innovation (Li, Nicholls, and Roslow, ). Despite the wealth of literature that has surfaced linking new product development to internationalization (Cassiman and Golovko, ; Lim, Sharkey, and Heinrichs, ), an interesting observation is that the majority of these studies have focused on the internationalization behaviors of the firm as a whole, rather than the internationalization of the individual new product innovation. Furthermore, the understanding of factors that influence the speed of international entry for an individual new product innovation remains elusive.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…The pressure to launch a new product concurrently or ahead of competitors in local and foreign markets is motivated by the emergence of global buyer segments, fear of technological obsolescence, and need for industry leadership in product innovation (Li, Nicholls, and Roslow, ). Despite the wealth of literature that has surfaced linking new product development to internationalization (Cassiman and Golovko, ; Lim, Sharkey, and Heinrichs, ), an interesting observation is that the majority of these studies have focused on the internationalization behaviors of the firm as a whole, rather than the internationalization of the individual new product innovation. Furthermore, the understanding of factors that influence the speed of international entry for an individual new product innovation remains elusive.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…It is suggested that NPD performance could be improved through cross-functional data creation and diffusion (Lim et al, 2003). Indeed, TMT members respond to various signals from domestic, international markets and competitors; they are able to equip the organisation with competencies through analysing information and making effective decisions to tune new products for different markets as a part of the internationalisation process (Lim et al, 2003). This approach could be useful exactly in terms of idea generation and market research as well as resource facilitation.…”
Section: Resultsmentioning
confidence: 99%
“…Different studies have been done in the past two decades on identifying critical success or failure factors of NPD with different methodologies (e.g., Cooper and Kleinschmidt, 1995;Spivey et al, 1997;Montoya-Weiss and Calantone, 1994;Cooper and Edgett, 2006;Holland et al, 2000;Ebrahimi et al, 2006;Sun and Wing, 2005;Cooper and Kleinschmidt, 2007;Lim et al, 2003), discovered various factors, and achieved diverse outcomes; however, valuable but sometimes conflicting, or even contradictory with the results of other studies (Afonso et al, 2008). Moreover, there are some studies (e.g., Ernst, 2002) which present a review of other studies in the field of NPD.…”
Section: Background and Hypotheses Developmentmentioning
confidence: 99%
“…Segundo Karagozoglu & Brown (1993) e Droge et al (2004) a competição baseada no tempo tem recebido muita atenção na literatura e na indústria. Lim et al (2003), destacam que os clientes esperam que novos produtos sejam desenvolvidos, ainda mais rapidamente do que antes e, neste ambiente a empresa deve explorar todas as oportunidades disponíveis para encurtar o tempo de comercialização desses novos produtos.…”
Section: Periódicosunclassified